2015
DOI: 10.1055/s-0035-1545982
|View full text |Cite
|
Sign up to set email alerts
|

Sonoran Propolis and Some of its Chemical Constituents Inhibit in vitro Growth of Giardia lamblia Trophozoites

Abstract: Propolis is a cereus resin with a complex chemical composition that possesses a wide range of biological activities. The aim of this study was to evaluate the in vitro anti-Giardia lamblia activity of Sonoran propolis collected from three different areas of Sonoran Desert in northwestern Mexico (Caborca, Pueblo de Alamos, and Ures) and some of its chemical constituents. Additionally, we also analyzed the seasonal effect on the anti-G. lamblia activity of propolis. G. lamblia trophozoite cultures were treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 31 publications
(47 reference statements)
2
19
0
Order By: Relevance
“…125.0 µg/mL)] presented significant differences, which suggested that slightly quantitative variations on the bioactive constituents could be implicated in the seasonal effect of biological activities of UP. All propolis samples had weak FRS activity (<25% at 100 µg/mL) [34,94].…”
Section: Mexicomentioning
confidence: 98%
See 2 more Smart Citations
“…125.0 µg/mL)] presented significant differences, which suggested that slightly quantitative variations on the bioactive constituents could be implicated in the seasonal effect of biological activities of UP. All propolis samples had weak FRS activity (<25% at 100 µg/mL) [34,94].…”
Section: Mexicomentioning
confidence: 98%
“…UP showed the highest growth inhibitory effect (IC 50 : 63.8 µg/mL) in comparison with CP and PAP (IC 50 : >200 µg/mL). Among the chemical constituents of Sonoran propolis evaluated, CAPE had the highest growth inhibitory activity (IC 50 : 222.1 µM), followed by naringenin (IC 50 : 461.8 µM), hesperetin (IC 50 : 494.9 µM) and pinocembrin activity (IC 50 : 680.6 µM) [34].…”
Section: Mexicomentioning
confidence: 99%
See 1 more Smart Citation
“…Several experiments and clinical investigations have shown the antiparasitic and adjuvant properties of the hydroalcoholic extract of propolis (HEP). HEP of different types of propolis showed antiparasitary efficacy against Giardia lamblia [ 20 , 21 ], Toxoplasma gondii and Trichomonas vaginalis [ 22 ]. It is important to highlight that T .…”
Section: Introductionmentioning
confidence: 99%
“…CAPE is a propolis constituent that has gained attention due to its broad pharmacological activities , including antibacterial, antiproliferative, antiparasitic and antioxidant effect, among others (Wang et al, 2014;Alday-Provencio et al, 2015). CAPE is more biologically effective than other natural hydroxycinnamic acid derivatives because of its structural properties, possessing better bioavailability in lipophilic systems due to its partition coefficient .…”
Section: Discussionmentioning
confidence: 99%